Surface plasmon mediated nonradiative energy transfer and enhanced radiative emission in stratified planar nanostructures - Golmakaniyoon, Sepideh (2017)
Planar plasmonic nanostructures have gained considerable attention due to their crucial role in the theoretical comprehension of surface enhanced fluorescent along with their wide applications in nonradiative energy transfer (NRET), plasmonic wave guided mode, Raman scattering spectroscopy, color filters, light emitting and light harvesting devices. With the availability of large density of states at the metallic surface, the radiative and nonradiative decay channels of an electric dipole in a vicinity of metal would be dramatically modified. However, the radiative enhancement cannot be realized for any desired emissive dipole as the existing plasmonic resonance frequency is limited to the well-known plasmonic materials. Despite the fact that recent studies in metamaterial structures demonstrate a promising approach of tuning Purcell factor across the emission wavelength, the structures still suffer from an inefficient radiative emission. Moreover, in the case of nonradiative energy transfer, the conventionally sandwiched donor-metal film-acceptor configurations lack the desired efficiency and suffer poor photoemission due to the high energy loss. In this dissertation, we propose and demonstrate the nonradiative energy transfer mechanism between the donor and the acceptor through multi-layered metallic nanostructures – stratified configuration, in which an efficient energy transfer can be realized. This novel approach in NRET uniquely provides us with the ability to overcome the drawback of high energy absorption losses in a thick metal film by inserting a non-absorbing dielectric layer between two thin metal films. Moreover, a strong plasmon-plasmon near-field coupling through the dielectric spacer layer is proven to profoundly extend the effective energy transfer distance/efficiency. The proposed architecture has been demonstrated through theoretical modeling and experiment. A full theoretical model of an oscillating dipole behavior in front of the planar plasmonic nanostructure is given to calculate the radiative and nonradiative decay rates, radiative emission enhancement, electric field enhancement factor and nonradiative energy transfer. We present the results for the two most applicable plasmonic materials, silver and gold, and develop the model from the conventional metallic nanostructure to the stratified metal-dielectric-metal configuration, in which a remarkably enhanced energy transfer efficiency is obtained as a result of stronger surface plasmon coupling at the metal-dielectric boundaries as evidenced by the enhanced electric field enhancement factor. Moreover, we present the theoretical and experimental demonstration of engineering surface plasmon mode to tune the maximum radiative decay rate frequency of an emitting dipole in a vicinity of a stratified metal-dielectric-metal nanostructure. This effect arises from an efficient surface plasmon coupling at the metal-dielectric interfaces that leads to the highest electric field enhancement at the dipole position in an optimized cascaded nanostructure. The design principle allows modifying the structure to obtain a maximum transmission efficiency at any desired frequency. The current approach uniquely provides the ability to get the highest plasmonic mode outcoupling to the far field emission at the interfaces by adjusting variable parameter including dielectric layer thickness and refractive index. Thanks to the effective cascaded plasmonic modes coupling across the metal-dielectric interfaces, the proposed design uniquely illustrate the ability to optimize the plasmonic nanostructure for noticeable radiative transmission and emission enhancement. In summary, this dissertation studies nonradiative energy transfer and radiative emission in the stratified plasmonic metal-dielectric nanostructures both numerically and experimentally. Our findings show that multilayer plasmonic configurations enhance the nonradiative energy transfer because of the strong surface plasmon near-field coupling created at the interfaces. Furthermore, we demonstrate the leading role of the decay rate improvement over the negligible contribution of excitation enhancement in the proposed stratified nanostructures. Exploiting this effect in light emitting devices, biosensors, and surface-enhance Raman spectroscopy may lead to structures with high radiated intensity at any desired emission frequency.